Mental health status after living donor hepatectomy. Issue 19 (May 2017) - Wang, Szu-Han; Lin, Ping-Yi; Wang, Jiun-Yi; Huang, Mei-Feng; Lin, Hui-Chuan; Hsieh, Chia-En; Hsu, Ya-Lan; Chen, Yao-Li
Abstract : Abstract: Donor safety and preservation of donor health after living liver donation are of paramount importance. In addition, the preoperative mental state of a donor is an important factor in determining the psychological impact of donor hepatectomy. Thus, we aimed to explore the mental health status of living liver donors after hepatectomy. We enrolled 60 donors who were scheduled to undergo living donor hepatectomy during the period January 2014 to March 2015 at a single medical center. Mental health status was measured before and 3 months after surgery using 3 self-report questionnaires, namely the Center for Epidemiologic Studies Depression Scale (CES-D) to assess depressive symptoms, the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire to measure quality of life, and the Chinese Health Questionnaire (CHQ) to screen for minor psychiatric disorders. A comparison of the pre- and postdonation CES-D scores revealed a significant reduction in depressive symptoms after surgery ( P  = .031). There were significant improvements in the physical health domain ( P  = .031), the psychological health domain ( P  = .005), the social relationships domain ( P  = .005), and the environmental health domain ( P  = .010) of the WHOQOL-BREF. There were no significant changes in CHQ scores after donor hepatectomy ( P  = .136). All donors reported that they would donate again if required. Approximately one-third (33.3%) of donors experienced more pain than they had anticipated in the immediate postoperative period, and 20.0% of donors had complications after donor hepatectomy. Donor mental health status tended to improve as donors regained physical function during the 1st 3 months of recovery. Long-term monitoring of living donors' mental health is needed to minimize the adverse psychological outcomes of living liver donation.